Short communication: Germination monitoring of selected Annonaceae seeds: Seed bank collections of Purwodadi Botanic Garden, East Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Pratiwi A, Lestari DA, Romdhonah Y. 2022. Short communication: Germination monitoring of selected Annonaceae seeds: Seed bank collections of Purwodadi Botanic Garden, East Java, Indonesia. Biodiversitas 23: 3567-3572. Monitoring activities are an essential aspect to determine the viability and germination of seeds after storage for a certain period. The seed bank of Purwodadi Botanic Garden collected 20 seeds of 11 different species of Annonaceae. Therefore, this study aimed to examine the seed viability of 11 selected species of Annonaceae after being stored for a certain time. Twenty seeds with three replications, i.e., 60 seeds in total were sown. Meanwhile, for genera of Uvaria consisted of U. purpurea, U. rufa, and Uvaria sp. were sown at 30 seeds in total, which means 10 seeds with three replications. The observed parameters were percentage of germination, seed viability, initial germination, and germination type. The results showed only 4 out of 11 selected species of Annonaceae were germinated, namely A. montana, F. latifolium, U. micranthum, and U. purpurea. These four species have epigeal germination types, and monitoring activities included stock rejuvenation, and evaluation of storage procedures for Alphonsea javanica, Annona glabra, Orophea enneandra, Polyalthia littoralis, U. rufa, and Uvaria sp. Furthermore, P. longifolia requires collection regeneration due to its recalcitrant character, and the number of empty seeds from the cut test was >75%. We suggested that P. longifolia seeds might be better to be stored in the refrigerator.